أقوال الإمام أبي عمرو بن العلاء في التفسير: جمعا ودراسة - مداح، أبو بكر الصديق; عواد، حمزة Awwad, Hamzah (جامعة الشهيد حمّه لخضر الوادي - معهد العلوم الإسلامية, 2023)
يهدف هذا البحث إلى جمع أقوال الإمام أبي عمرو بن العلاء في التفسير، وذلك من خلال كتب اللغة والتفسير والمعاني، ابتدئ البحث بمقدمة للتعريف بالموضوع وأهميته، ثم تمهيد تضمن ترجمة أبي عمرو بن العلاء، ثم بعد ذلك دراسة أقواله في التفسير. وأكد هذا البحث على مدى حرص أبي عمرو على عدم مخالفة تفسير السلف من الصحابة والتابعين، ومدى حرصه أيضا على العناية باللغة؛ لأنها من أهم مصادر تفسير القرآن الكريم، كما أكد البحث على أن أقوال أبي عمرو قد وافقت أقوال عامة المفسرين واللغويين. The aim of this research is to collect the statements of Imam Abu Amr Ibn Al Ala' regarding interpretation, through the language, interpretation, and meanings books, The research begins with an introduction to define the topic and its importance, followed by a prelude that includes a biography of Abu Amr Ibn Al-Ala', followed by a study of his statements on interpretation. The research emphasizes Abu Amr's keenness not to contradict the interpretation of the Salaf from the Companions and the Tabi'een, as well as his keenness on language care, as it is one of the most important sources of interpreting the Holy Quran. Additionally, the research confirms that Abu Amr's statements agree with those of the majority of interpreters and linguists.
Keywords: التميمي، بن العلاء بن عمار، ت. 154 هـ. -- علم التفسير -- القرآن الكريم -- علماء الإسلام